2016
DOI: 10.1007/s13280-016-0817-2
|View full text |Cite
|
Sign up to set email alerts
|

Rumours about wildlife pest introductions: European rabbits in Spain

Abstract: Rumours associated with wildlife are frequent, although they have received little attention in the scientific literature. Studying rumours is important because of their relevance not only in a broad theoretical sense but also in environmental management. The goal of this study is to explore the complexity of the relationships between humans and wildlife through a thematic analysis of rumours associated with allegedly introduced European rabbits (Oryctolagus cuniculus) that cause crop damage in Spain. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…33 Despite this, media reports have been successfully used previously to assess the impact of small mammal pests. 34 Thus, we argue that, even if there is some error involved, the information obtained in our study can help identify areas of potential stakeholder conflict regarding the management of pest species (farmers and hunters in our study model), 18,24 and can be used in the design of more realistic management plans.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…33 Despite this, media reports have been successfully used previously to assess the impact of small mammal pests. 34 Thus, we argue that, even if there is some error involved, the information obtained in our study can help identify areas of potential stakeholder conflict regarding the management of pest species (farmers and hunters in our study model), 18,24 and can be used in the design of more realistic management plans.…”
Section: Discussionmentioning
confidence: 93%
“…We selected this word combination based on a previous study which showed that this permutation, but also “rabbit” and “damage”, worked better than “rabbit” and “crop”, and “rabbit” and “overpopulation” . The first 600 consecutive sites resulting from our Google search were visited and their content evaluated by M. Delibes‐Mateos . Searches were performed between 18 May and 11 June 2015.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Campbell‐Smith et al., 2010), including our study areas, and it is a way to legitimise intensive population control. In addition, multiple Spanish media articles demand effective responses to crop damage caused by ‘rabbit plagues’ (‘ plagas de conejo ’ in Spanish) in farmland areas (Delibes‐Mateos, 2017), which therefore disseminate and legitimise the message that farmers expressed in our interviews.…”
Section: Discussionmentioning
confidence: 99%